Padronização da micro e nanodureza por penetração instrumentada - Renato Reis Machado (2005)
The measurements of conventional indentation hardness (Brinell, Rockwell, Vickers and Knoop) are known and their methods were normalized more than 50 years ago. Their results are numbers that represent the size of the residual impressions into the sample surface after the indentation. Face to the scientific and technological demands, different methods were developing for the characterization of hardness and other mechanical material properties in micro and nanometer levels. A new method proposed for hardness and material parameters should provide advances in the comparison with the conventional methods to achieve success. The method known as "Measurement of Hardness and Materials Parameters for Instrumented Indentation Test is based on the use of diamond or hard metal indenters to indent the sample surface, with forces and indentation depths measured and presented simultaneously through a graphic. With this technique, is possible to characterize the plastic and elastic behavior of a material with the minimum operator influence. The method appeared as a tool for the mechanical characterization of materials and it has to be shown as an important technique in the development of thin films, nanostructural and ceramic material, etc, for its speed and capacity to determine these properties independently from hardness. This method is frequently the only one which it makes possible the research of properties in tiny areas of materials (< 200 nm). However, up to this moment, an established process doesn't exist for the warranty of the metrological chain of these measurements. For that, it is crucial that the harmonization should carry out by these measurements in the international scale levels. That starting from the determination of standard reference materials, the elaboration of procedures and the development of appropriate techniques for the correct realization of these measurements and its respective application. Four oxide glasses with different ranges of hardness and indentation elastic modulus, were selected throughout theirs use on the calibration of the indenter area function and the frame machine compliance and theirs use on the performance verification of the equipments to be used in the interlaboratorial comparisons of instrumented indentation test for micro and nanoindentation, seeking theirs qualification as a reference materials.